Comparing the Effectiveness of Online and In-Person English Language Instruction on Students’ Speaking Proficiency - Sohrabi, Alireza; Hassanpour , Bita; Jafari Saleh, Arshia (Assessment and Practice in Educational Sciences, 2026)
This study aimed to explore and compare how learners perceive the effectiveness of online and in-person English language instruction in developing their speaking proficiency, focusing on their experiences, challenges, and perceived progress in each modality. A qualitative research design was employed to capture in-depth insights into learners’ experiences. Nineteen English language learners (10 females, 9 males; aged 18–32) from private language institutes in Tehran, Iran, participated in the study. Participants were selected through purposive sampling to ensure variation in gender, proficiency level, and learning mode. Data were collected through semi-structured interviews that explored learners’ perceptions of instructional effectiveness, interaction quality, feedback, motivation, and confidence in speaking. Interviews were transcribed verbatim and analyzed using thematic analysis with NVivo 14 software. The coding process continued until theoretical saturation was reached, resulting in the emergence of four main themes and multiple subthemes. Analysis revealed that both online and in-person instruction contributed to speaking proficiency through distinct mechanisms. In-person classes enhanced fluency, pronunciation, and pragmatic competence through immediate feedback, peer interaction, and teacher presence. Online instruction promoted learner autonomy, reflective practice, and pronunciation monitoring through digital tools such as speech recognition and recorded feedback. Teacher support, engagement strategies, and feedback modality significantly influenced learners’ motivation and willingness to communicate. Despite technological challenges, participants appreciated the flexibility and self-paced nature of online learning, while many expressed a preference for hybrid models that integrate both approaches for optimal results. Both online and in-person English instruction are effective for improving speaking proficiency when pedagogical design, feedback mechanisms, and learner engagement are appropriately balanced. Integrating the social richness of classroom interaction with the flexibility of digital tools can create a more holistic and learner-centered model for developing oral competence in EFL contexts.